The Ethics of Reconciling: Learning from Canada’s Truth and Reconciliation Commission - Snyder, Emily (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2010)
In 2008, the Truth and Reconciliation Commission of Canada (TRC) was initiated to address the historical and contemporary injustices and impacts of Indian Residential Schools. Of the many goals of the TRC, I focus on reconciliation and how the TRC aims to promote this through public education and engagement. To explore this, I consider two questions:who does the TRC include in the process of reconciliation? Andhow might I, as someone who is not Indigenous (specifically, as someone who is “white”), be engaged by the TRC?Ethical queries arise which speak to broader concerns about the TRC’s capability to fulfill its public education goals. I raise several concerns about whether the TRC’s plan to convoke the collective will result in over-simplifying the process by relying on blunt, poorly defined identity categories that erase the heterogeneity of those residing in Canada, as well as the complexity of the conflict among us. I attempt to situate myself in-between proclamations of “success” or “failure” of the TRC, to better understand what can be learned from contested truths and experiences of uncertainty.